2004
DOI: 10.1161/01.cir.0000136999.77584.a2
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Induces Apoptosis in Human Coronary Vascular Smooth Muscle Cells

Abstract: SUMMARYBehavior and physiology are regulated by both environment and social context. A central goal in the study of the social control of behavior is to determine the underlying physiological, cellular and molecular mechanisms in the brain. The African cichlid fish Astatotilapia burtoni has long been used as a model system to study how social interactions regulate neural and behavioral plasticity. In this species, males are either socially dominant and reproductively active or subordinate and reproductively su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
87
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(96 citation statements)
references
References 116 publications
8
87
1
Order By: Relevance
“…Some previous studies indicated that RNAi was induced in vitro into rat cardiomyocytes [39] as well as in human coronary vascular smooth muscle cells [40] in culture. We also demonstrated successful sequencespecific knockdown of endogenous gene expression in vivo in the coronary artery of adult mice using siRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies indicated that RNAi was induced in vitro into rat cardiomyocytes [39] as well as in human coronary vascular smooth muscle cells [40] in culture. We also demonstrated successful sequencespecific knockdown of endogenous gene expression in vivo in the coronary artery of adult mice using siRNA.…”
Section: Discussionmentioning
confidence: 99%
“…CRP can directly inhibit differentiation, survival and functions of endothelial progenitor cells, which are key components of angiogenesis and the response to chronic ischemia [25]. CRP can induce apoptosis in human coronary vascular smooth muscle cells [26]. CRP can also suppress neutrophil activity [27].…”
Section: Introductionmentioning
confidence: 99%
“…7 CRP is a chemoattractant for monocytes, 8,9 upregulates adhesion molecules, 10 and decreases NO release by endothelial cells, 6,11 induces plasminogen activator inhibitor type 1 expression 12 and tissue factor synthesis by vascular smooth-muscle cell (VSMC) and endothelial cells 13 and exhibits both proliferative and apoptotic properties on vascular cells. 13,14 Finally, CRP increases matrix metalloproteinase-1 in monocytic cells in culture suggesting that it could promote matrix degradation and thus contribute to plaque vulnerability. 15 Extra-hepatic synthesis of CRP has been reported in alveolar macrophages, neurons, lymphocytes, and in vascular cells.…”
mentioning
confidence: 99%